2019
DOI: 10.2337/ds18-0057
|View full text |Cite
|
Sign up to set email alerts
|

Yours, Mine, and Ours: A Qualitative Analysis of the Impact of Type 1 Diabetes Management in Older Adult Married Couples

Abstract: he incidence of type 1 diabetes is rising (1), as is the number of older adults (>65 years of age) who are living with type 1 diabetes (2). The life expectancy of individuals diagnosed with type 1 diabetes increased by 15 years between 1950-1964 and 1965-1980 (3). Type 1 diabetes is associated with a number of health complications, including myocardial infarction, cerebrovascular accidents, retinopathy, neuropathy, nephropathy (4), hypoglycemia and hypoglycemia unawareness (5), and dementia-all of which are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…One way to augment DSMES would be to include caregivers (eg, parents) and care partners (eg, spouses, family, friends). 59 In a systematic review by Baig and colleagues, 60 family involvement was found to have positive impact on other outcomes including improved self-care, self-efficacy, knowledge, and perceived social support. Furthermore, among adults newly diagnosed with T2DM, family involvement in diabetes education was shown to be beneficial for glucose levels, knowledge and attitudes, and quality-of-life outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One way to augment DSMES would be to include caregivers (eg, parents) and care partners (eg, spouses, family, friends). 59 In a systematic review by Baig and colleagues, 60 family involvement was found to have positive impact on other outcomes including improved self-care, self-efficacy, knowledge, and perceived social support. Furthermore, among adults newly diagnosed with T2DM, family involvement in diabetes education was shown to be beneficial for glucose levels, knowledge and attitudes, and quality-of-life outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review by Baig et al 60 of family interventions to improve general outcomes in adults with T2DM provided no reports on hypoglycemia-related outcomes; however, a recent study of older adults indicated that care partners can be heavily involved in hypoglycemia mitigation, and targeted interventions may further support hypoglycemia prevention. 59…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experience of being a partner or family member of someone with Type 1 diabetes has also been extensively explored [10,11]. Recent qualitative work with couples living with Type 1 disease has compared perspectives of what constitutes diabetes support, revealing some distinctions between how people with Type 1 diabetes and their partners make sense of adequate self-care [12]. The study also suggested that people with Type 1 diabetes are not always aware of the extent to which diabetes affects their partner; however, the extent to which partners are aware of the emotional struggles experienced by people with Type 2 diabetes is less understood.…”
Section: Introductionmentioning
confidence: 99%
“…11 For example, there may be challenges due to discordant appraisal of diabetes responsibility, resulting in relationship tension among couples. 12 There are also instances when a fifth type of support, invisible, is offered and PWD are not aware that it is being offered. Family members and/or friends of PWD can benefit from training by diabetes care and education specialists and other HCPs on how they may optimally provide ongoing support.…”
Section: Types Of Diabetes Supportmentioning
confidence: 99%